Molecular dynamics simulations on dihydroxylammonium 5, 5′-bistetrazole-1, 1′-diolate/hexanitrohexaazaisowurtzitane cocrystal. Issue 5 (7th January 2016) - Xiong, Shuling; Chen, Shusen; Jin, Shaohua; Zhang, Chunyuan
Abstract : Dihydroxylammonium 5, 5′-bistetrazole-1, 1′-diolate (TKX-50) is a newly synthesized explosive with excellent comprehensive properties, and TKX-50/ε-CL-20 cocrystal has been proved to form by molecular dynamics simulations. Abstract : Dihydroxylammonium 5, 5′-bistetrazole-1, 1′-diolate (TKX-50) is a newly synthesized explosive with high detonation performance, low impact sensitivity and low toxicity. Hexanitrohexaazaisowurtzitane (CL-20), especially ε-CL-20, is currently the highest energy-density explosive. The research on the TKX-50/ε-CL-20 cocrystal can improve the defects of single-compound explosives in their application and greatly expand the application range of TKX-50 and CL-20. Seven TKX-50/ε-CL-20 cocrystal models were constructed, and the radial distribution function (RDF), X-ray powder diffraction (XRD) and energy calculation were analyzed based on the equilibrium structures of the cocrystal models by molecular dynamics (MD) simulations. The results indicate that the diffraction peaks of the TKX-50/ε-CL-20 cocrystal quite differ from TKX-50's and ε-CL-20's and new structure forms, hydrogen bond interactions and van der Waals forces exist in the TKX-50/ε-CL-20 cocrystal structure, and the cocrystal model of TKX-50 substituted by ε-CL-20 on its [011] facet is easiest to form.